miniMuTe: A muon telescope prototype for studying volcanic structures with cosmic ray flux - Peña Rodríguez, Jesus (Scientia et Technica, 2018)
The Muon Telescope (MuTe) project is developed by the Universidad Industrial de Santander in collaboration with the Universidad del Tolima, the Servicio Geológico Colombiano and supported by Colciencias; the detector will be placed at the Cerro Machin Volcano located in South-West of Colombia. MuTe records the muonic component flux of secondary cosmic rays (CRs) passing through geological formations, for imaging their inner structure depending on their differences in density. For testing the hodoscope electronic readout a prototype of 9 pixels (miniMuTe) was developed. In this paper, the measurement of the background flux of CRs at Cerro Machin Volcanoe, carried out with the miniMuTe prototype, is presented.